On-line, but off target? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
workshop in Abidjan, Côte d'Ivoire, in November 1998, in collaboration with the West Africa Rice Development Association (WARDA).